A decision-making framework for designing water distribution networks based on multi-objective optimisation. (2016) - Yazdandoost, Farhad; Izadi, Ardalan
Multi-objective optimisation of water distribution networks (WDNs) design would be an effective step towards the proper management of these infrastructures. This in turn depends upon how well the decision maker (DM) identifies the trade-off between the objectives. Here, a three-step framework is proposed to address this challenge. Part of the WDN in Iran, has been optimised by NSGA-II based on cost and resilience index (RI) objectives. The obtained non-dominated solutions located on the Pareto front were then processed through the entropy method to quantify the weights for the objectives while considering the preferences of the DM. Finally, the TOPSIS method was used to determine the best choice. The results, compared to those proposed by the original design consultants and cost-benefit analysis (CBA), show that the current proposed framework can be used as a more reliable tool to verify WDNs cost-benefit analysis while creating a better balance between the objectives.